Histopathological features of oral lichen planus and its response to corticosteroid therapy: A retrospective study - Anitua, Eduardo (Medicine (Baltimore), 2019)
Oral lichen planus (OLP) exhibits variations in severity and response to corticosteroid therapy. This study aims to assess the histopathological features of OLP at the time of diagnosis and their relationship in response to corticosteroid therapy. In this retrospective study, OLP patients were selected if a histopathological report was available. Data were collected regarding patients’ demographics and medical history. Clinical and histological data were also obtained. The outcomes were histopathological findings, clinical form of OLP, number of exacerbations per year, and the response to corticosteroid therapy. In this study, 100 OLP patients were enrolled. Basal layer hydropic degeneration and band-like subepithelial lymphocytes infiltrate were observed in all patients. Plasma cells, identified in 62% of OLP patients, were significantly associated with fewer disease exacerbations and better response to corticosteroid treatment. Identifying histopathological features that may affect the clinical course would be clinically helpful in tailoring patient management.